The Financial Performance of European Companies: Explanatory Factors in the Context of Economic Crisis - Madaleno, Mara; Barbuta-Misu, Nicoleta (Ekonomika, 2019)
Financial accounting information plays an important role in assessing and forecasting firms’ financial performance. But besides that, there are other external factors affecting the performance of firms, such as economic and financial crises, which cause imbalances over the economy and affects the business environment. Thus, based on financial statements data, in this paper, the determinants of financial performance are examined, and the impact of a financial crisis on these factors is analyzed, using the fixed and random effects panel estimators. A sample of non-financial firms from European countries considering annual data for the period of 2006 to 2015 was used for this research. The results achieved by panel data analysis show that a crisis exerts a significant positive effect over financial performance as well as liquidity, assets turnover, and labor productivity, meaning that firms tend to put in greater efforts to maintain financial performance in the face of a crisis. Financial performance is significantly and negatively influenced by leverage independently of the crisis effect, showing return on assets to be lower than the average interest rate.